2007
DOI: 10.1007/s00264-007-0326-9
|View full text |Cite|
|
Sign up to set email alerts
|

Foot pumps without graduated compression stockings for prevention of deep-vein thrombosis in total joint replacement: efficacy, safety and patient compliance

Abstract: Mechanical prophylaxis with foot pumps provides an interesting alternative to chemical agents in the prevention of thromboembolic disease following major orthopaedic surgical procedures. Recent studies have suggested that the simultaneous use of graduated compression stockings (GCS) may hinder the pneumatic compression effect of foot pumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…As reported by others, we found that 4/6 subjects among those requiring the early discontinuation of the compression attributed it to the noise. This is consistent with the few data from the literature showing that sleep disturbances attributed to noise was the more frequent reason (69-81%) for premature termination [16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 81%
“…As reported by others, we found that 4/6 subjects among those requiring the early discontinuation of the compression attributed it to the noise. This is consistent with the few data from the literature showing that sleep disturbances attributed to noise was the more frequent reason (69-81%) for premature termination [16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 81%
“…3 A-V Impulse foot pumps are effective and safe in THR. 11,13,15 After TKR, the effectiveness of foot-pumps is less certain, with some studies reporting a benefit, whereas other did not. 4,17,18 To our knowledge, this is the first prospective trial performed to establish efficacy and safety of the Flowtron ® foot pump system, a widely used device, but apparently not sufficiently validated in clinical settings.…”
Section: Discussionmentioning
confidence: 96%
“…In some patients, the surgeon advised use of foot-pumps without simultaneous application of antithrombotic stockings. 11,16 Various chemicals were prescribed in combination with the foot-pumps. However, in some young and healthy patients the surgeon elected to use only foot pumps for prevention of venous thromboembolism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite positive results, compliance remains a barrier to effective foot pump use due to complaints of disturbed sleep and decreased mobility [60][61][62]. Charalambous et al [60] assessed compliance in 29 patients after TKA or THA, and found that they were worn, applied properly, and functioning correctly only in 37% of observations (n = 231 of 621).…”
Section: Foot Pumpmentioning
confidence: 97%